STUDENTS’ ATTITUDES TOWARD USING ARTIFICIAL INTELLIGENCE TOOLS IN LEARNING ENGLISH IN UZBEKISTAN. (Ustozlar uchun, 2026)
Artificial Intelligence (AI) has become an important part of modern education, offering learners new opportunities to improve their knowledge and skills. In English language learning, AI-powered tools such as ChatGPT, Grammarly, Google Translate, and Duolingo provide students with instant feedback, personalized learning experiences, and access to educational resources. This study investigates the attitudes of Uzbek students toward using AI tools in learning English. A questionnaire was conducted among 30 university students who actively study English. The findings reveal that most students have positive attitudes toward AI tools because they improve vocabulary, grammar, writing, and speaking skills. Participants also reported that AI applications increase motivation and support independent learning. However, concerns about overreliance on technology and inaccurate information were also identified. The study concludes that AI tools can effectively support English language learning when used responsibly and alongside traditional learning methods.